Vaccinia virus in feces and urine of wild rodents from São Paulo State, Brazil - Peres, Marina G. [UNESP]; Bacchiega, Thais S. [UNESP]; Appolinário, Camila M. [UNESP]; Vicente, Acácia F. [UNESP]; Mioni, Mateus S. R. [UNESP]; Ribeiro, Bruna L. D. [UNESP]; Fonseca, Clóvis R. S. [UNESP]; Pelícia, Vanessa C. [UNESP]; Ferreira, Fernando; Abrahão, Jonatas S.; Megid, Jane [UNESP] (MDPI, 2018)
The origin of Vaccinia virus (VACV) outbreaks in Brazil remains unknown, but since the isolation of VACV in Mus musculus mice during a zoonotic outbreak affecting cattle and milkers, peridomestic rodents have been suggested to be a link between cows and wild animals. Considering that experimentally infected mice eliminate viral particles in their feces, we investigated the presence of VACV in the feces and urine of wild rodents that were captured in the forest areas surrounding milking farms in the central west region of São Paulo State. For the first time, this work reports the detection of VACV by PCR in the feces of naturally infected Oligoryzomys flavescens, Oligoryzomys nigripes, and Sooretamys angouya, and in the urine of Oligorizomys flavescens, which raises important questions about the spread of VACV by rodent feces and its potential to induce clinical infections in cows.
Keywords: Epidemiology; PCR; Public health; Transmission; Vaccinia virus; Wild animals